Pengaruh Edukasi Berbasis Aplikasi Mother Care (MOCA) terhadap Pengetahuan Tugas Ibu Tentang Perkembangan Anak Usia Prasekolah - Uswatun Mahmudah; Arifal Aris; Suhariyati Suhariyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Low maternal knowledge regarding preschool children’s developmental tasks may contribute to developmental delays and suboptimal child growth outcomes. Technological developments have encouraged the use of digital educational media to improve maternal understanding, one of which is the Mother Care (MOCA) application. This study aimed to analyze the effect of education based on the Mother Care (MOCA) application on maternal knowledge regarding preschool child development tasks. This research used a pre-experimental design with a one-group pretest-posttest approach. The population consisted of all mothers who had preschool-aged children in Tunggunjagir Village, Mantup District, Lamongan Regency. A total of 60 respondents were selected using a total sampling technique. The research instrument was a knowledge questionnaire containing positive and negative statements related to maternal developmental tasks and the MOCA application as educational media. Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed that before the intervention, 46.7% of respondents had low knowledge levels, while after the intervention, 76.7% of respondents had good knowledge levels. Statistical analysis showed a significant difference in maternal knowledge before and after the intervention with p-value = 0.001 (p < 0.05). The findings indicate that education through the MOCA application significantly improves maternal knowledge regarding preschool child development tasks. Digital education through mobile applications can therefore be used as an innovative and effective educational strategy in community nursing services.